2015
DOI: 10.1186/s12903-015-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

S100, bcl2 and myeloperoxid protein expirations during periodontal inflammation

Abstract: BackgroundPeriodontal inflammation is characterized by injuries in collagen, epithelial, bone tissues. The hypotheses to be tested were relationship between the s100, bcl2 and myeloperoxidase in gingival tissues (MPO does affect the level of s100, bcl2). The object of this study was to investigate of s100 expression, bcl2 expression and myeloperoxidase expression in periodontal inflammation.Methods27 patients (giant-cell epulis) and 30 patients (acute and chronic inflammations) were included in the study for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(35 reference statements)
4
9
0
1
Order By: Relevance
“…In the future without timely intervention will lead to more severe damage of periodontal tissues, premature loss of teeth, and changes in temporomandibular joints. Results from the previous research indicate the role of periodontal pathological processes in the development of systemic inflammation [ 4–6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the future without timely intervention will lead to more severe damage of periodontal tissues, premature loss of teeth, and changes in temporomandibular joints. Results from the previous research indicate the role of periodontal pathological processes in the development of systemic inflammation [ 4–6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 family proteins regulate apoptosis through protein–protein interactions. Previous reports suggest that overexpression of Bcl‐2 inhibits apoptosis and plays an important role in the development of inflammation-related disorders 33 , 34 . Accordingly, these results suggest activation of a novel rno-miR-374-5p / Mex3B / Kras pathway to elevate cell viability in extreme hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have been carried out to delineate the pathogenesis of epulis and gingival hyperplasia. Several studies have found that apoptosis inhibition through overexpression of bcl‐2 might play an important role in the development of epulis . Extracellular matrix degradation and remodeling are also important aspects, and matrix metalloproteinases (MMPs) play an important role in periodontal tissue destruction …”
Section: Introductionmentioning
confidence: 99%
“…that apoptosis inhibition through overexpression of bcl-2 might play an important role in the development of epulis. [7][8][9] Extracellular matrix degradation and remodeling are also important aspects, and matrix metalloproteinases (MMPs) play an important role in periodontal tissue destruction. 10 Systems biology approaches such as whole-genome expression profiling may provide new insights into the molecular mechanisms of fibrous epulis.…”
mentioning
confidence: 99%